The metaphorical image in the poetry of the poets of the palace doll and the era of the people of the age: An analytical study - Ali, Walid Awaid Hussein; Abbas, Saja Jassim Muhammad (Al-Adab Journal, 2022)
The poetic image, especially the metaphor, is one of the topics that aroused the efforts of researchers and scholars in Arabic literature, ancient and modern, and took a literary and critical dimension alike, Because of its philosophical value that shows the ingenuity of poets and the value of their literary production, From this point of view, in this research, we monitored the metaphorical image in the poetry of the poets of the palace doll and the era of the people of the age by Al-Bakhrazi (467 AH), and how these poets were able to employ these images with unique poetic ingenuity and high stylistic sobriety, We worked to include the most poetic texts in their poems and the most ingenious in their meanings. The palace doll poets have a highly suggestive poetic language and have a tyrannical symbolism, and the subject of the poetic metaphor in their poems is one of the most present and evident images, and most emulates the reality of their social and psychological lives.